Eastman posts 3% sales increase in 3Q 2014. Issue 2 (February 2015) - Unknown
Abstract : For the third quarter of 2014, Eastman Chemical Co achieved sales revenue of US2.41 billion, a 3% increase compared with 2.34 billion in 3Q 2013. Excluding certain items, operating earnings for 3Q 2014 were 427 million compared with 405 million a year earlier, primarily due to increased earnings by the Advanced Materials and Adhesives & Plasticizers segments. The company's reported third-quarter 2014 operating earnings were 338 million compared with 479 million for the third quarter of 2013.